CONSTRUCTION AND RESEARCH OF THE NEURO AND INDISTINCT REGULATORS OF STREAMS OF THE SUBSTRATUM AND PRODUCT FOR OPERATED CONTINUOUS BIOSYSTEM - Aleksandr Andreevich Volodin; Elena Valeryevna Lubentsova; Valery Fedorovich Lubentsov (Вестник Северо-Кавказского федерального университета)
Results of research of dynamic characteristics of continuous biotechnological system by means of the de- veloped neuroindistinct regulators of streams of a substratum and a product are given at a variation of the fol- lowing characteristics of regulators: number and type of membership function, set of rules of the fuzzy control- ler. The analysis of the received results showed that when using fuzzy controllers reregulation in contours of regulation of streams of a substratum and a product 1,5-2 times smaller respectively, than when using not adap- tive regulators.